A uniform approach to test computational complementarity - Calude, Elena; Mills, Bruce; Mills, Lan (Acta Cybernetica, 2004)
Studies of computational complementarity properties in finite state interactive automata may shed light on the nature of both quantum and classical computation. But, complementarity is difficult to test even for small-size automata. This paper introduces the concept of an observation graph of an automaton which is used as the main tool for the design of an algorithm which tests, in a uniform manner, two types of complementarity properties. Implementations have been run on a standard desktop computer examining all 5-state binary automata.